PERBANDINGAN EFFECTIVE TAX RATE (ETR) DAN RASIO KOREKSI FISKAL TERHADAP ASET SEBAGAI INDIKATOR TAX AVOIDANCE - Handayani, Lidia Kristina; Murniati, Monika Palupi (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2023)
The study aims to prove the relationship between earnings management (return on asset, asset intensity, inventory intensity) and corporate governance (independent commissioners, audit committee) on tax avoidance, which is based on two measurements (effective tax rate and accounting profit minus taxable profit that divided by total asset). The sample in this study are 114 companies engaged in the manufacturing sector that listed on the Indonesia Stock Exchange (IDX). Method analysis used in this study is descriptive statistical analysis, classical assumption test and multiple linear regression analysis. The results of regression model shows that return on asset, asset intensity, inventory intensity, independent commissioners and audit committee have a significant determinant on the tendency of companies do tax avoidance. This study is expected to be useful for government, companies, and investors as a guide to make a better decision.